Therapeutic Applications of Mesenchymal Stem Cells in Idiopathic Pulmonary Fibrosis - Yang, Shengnan; Liu, Peipei; Jiang, Yale; Wang, Zai; Dai, Huaping; Wang, Chen (Frontiers in Cell and Developmental Biology, 2021)
Idiopathic pulmonary fibrosis (IPF) is an interstitial disease of unknown etiology characterized by progressive pulmonary fibrosis. Pirfenidone and nintedanib are the only drugs that can prolong the time to disease progression, slow down the decline in lung function, and prolong survival. However, they do not offer a cure and are associated with tolerability issues. The pluripotency of mesenchymal stem cells (MSCs) and their ability to regulate immunity, inhibit inflammation, and promote epithelial tissue repair highlight the promise of MSC therapy for treating interstitial lung disease. However, optimal protocols are lacking for multi-parameter selection in MSC therapy. This review summarizes preclinical studies on MSC transplantation for the treatment of interstitial lung disease and clinical studies with known results. An analysis of relevant factors for the optimization of treatment plans is presented, including MSCs with different sources, administration routes and timing, dosages, frequencies, and pretreatments with MSCs. This review proposes an optimized plan for guiding the design of future clinical research to identify therapeutic options for this complex disease.